Meteorological data from Röbäcksdalen Research Area, AWS, 2021-01-01–2021-12-31 - Röbäcksdalen Field Research Station (Swedish University of Agricultural Sciences, 2026)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Röbäcksdalen Field Research Station (2026). Meteorological data from Röbäcksdalen Research Area, AWS, 2021-01-01–2021-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/9yDk6K4xPxhgIKXiME0Hwkp8
Keywords: Röbäcksdalen Field Research Station; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Relative humidity; Relative humidity; Wind speed; Wind speed; Wind direction; Wind direction; Soil temperature; Soil temperature; Incoming shortwave radiation; Incoming shortwave radiation; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap